A Survey Paper on OSN User Wall to Filter Unwanted Messages - Bawane, Nasarin; Pise, Manisha (International Journal of Computer Sciences and Engineering, 2025)
One fundamental issue in today On-line Social Networks (OSN’s) is to give users the ability to control the messages posted on their own private space. To avoid that unwanted content is displayed. Until now OSN provides little support to this requirement. To fill this gap, in this project, we propose a system that allows a user to create our own blacklist, in this user get insert unwanted words which they don’t want on our wall. We provide user to customize the filtering criteria to be applied on to their walls.